Current Challenges in Sustainable Management of Local Energy Security in Reducing Heat Poverty - A Case Study of a Selected Region of Poland - Katarzyna ŚWIERSZCZ (Communications of International Proceedings, 2021)
The What prompted the author to explore this subject is the persistent phenomenon of heat energy poverty in households remaining at a fairly high level, in Poland, other more or less developed countries in Europe, as well as all over the world. There are three key factors behind this phenomenon: economic, technical, and attitude (awareness) aspects - between which there is an imbalance and a lack of further sustainability. Research shows that while local governments, who are responsible for the sustainable and effective energy security management, are starting to notice the problem of heat energy poverty, their actions taken to resolve it are often intuitive.  The author of the article has three main objectives. The first one is to define heat energy poverty and heat energy security. Secondly, to show the current situation of heat energy poverty, its causes and the consequences for households, based on a case study of the commune of Wiśniowa. The third objective is to present, based on the case study of the Wiśniowa commune, the actions taken by the Local Government Unit (JST) in terms of sustainable managing local heat energy security, the aim of which is to eliminate the problem of heat energy poverty in the area by investing in geothermal energy. The research problem addressed in the paper is theoretical and empirical. The research methods employed include: analysis, definition, synthesis, generalization and inference. The research undertaken and its results, apart from being a valuable statistical source, provide general insight which may serve as guidelines and recommendations for future actions to be taken by Local Government Units, both at the municipal and national level, in order to deal with challenges and to improve the strategies of sustainable managing local heat energy security.
Keywords: heat energy poverty; energy security; local government unit; energy security sustainable management; geothermal energy.